Effects on Bone Tissue After Osteotomy with Different High-Energy Lasers: An Ex Vivo Study - De Oliveira, Guilherme José Pimentel Lopes [UNESP]; Rodrigues, Conrado Nogueira Campelo [UNESP]; Perussi, Lívia Rodrigues [UNESP]; De Souza Rastelli, Alessandra Nara [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP]; Berbert, Fábio Luiz Camargo Villela [UNESP] (SAGE Publications, 2016)
Objective: The purpose of this study was to evaluate the application of Er:YAG and Er,Cr:YSGG lasers during osteotomy in bovine bone blocks. Background data: Er:YAG/Er,Cr:YSGG lasers for osteotomy procedures have been used to induce tissue ablation without thermal damage. However, even these lasers can induce thermal damages, which can cause a delay on the bone healing. Materials and methods: Sixty standardized bovine bone mandible samples were divided into three groups with 20 samples each: Group 1, Bur; Group 2, Er:YAG laser; and Group 3, Er,Cr:YSGG laser. Two irradiations/cuts were made in each sample. The first was performed until the sample was completely separated into two fragments, and the time required for this procedure was recorded in seconds. The second irradiation/cut was made the same way as the first one; however, it was made partially, without separating the sample into two fragments, but rather making sulci ∼1.5-2 mm deep. Ten samples in each group were used to evaluate the surface morphology of the osteotomy by scanning electron microscopy (SEM), while the other 10 samples were submitted to descriptive histological analysis. Results: The bur was the instrument that performed the osteotomy in the shortest amount of time (p < 0.05). All the instruments caused thermal damage; however, the Er,Cr:YSGG laser was the only type that induced carbonization. Conclusions: The Er:YAG laser induced the lowest degree of thermal damage in bone tissue after osteotomy; however, a shorter clinical time was required to perform the osteotomy in the bur group.